Hybrid effect of basalt fiber textile and macro polypropylene fiber on flexural load-bearing capacity and toughness of two-way concrete slabs - Ding, Y. (2020)
This paper presents an experimental study on the two-way concrete slabs with steel-free reinforcements. These include basalt fiber textile, macro polypropylene (PP) fiber and a combination of both. The plain concrete (PC) slab and steel reinforced concrete (RC) slab are studied as references. Furthermore, a comparative analysis on load bearing capacity, toughness and failure pattern of the slabs is performed. The test results indicate that the incorporation of basalt fiber textile and macro PP fibers can significantly improve load bearing capacity and toughness, and there is a positive synergetic effect between basalt fiber textile and macro PP fiber in the hybrid system. Similar to PC slab, the concrete slab reinforced with only 1-layer basalt fiber textile (BTRC1) demonstrates clearly brittle behavior. The addition of macro PP fibers may enhance the load bearing capacity in the post-peak region and convert the brittle failure pattern into a ductile one. In addition, BTRC1 slab with 8 kg/m3 macro PP fibers shows higher flexural capacity than those of RC slab with a steel ratio of 0.31%, and this implies that the combination of basalt fiber textile and macro PP fiber can be used to replace the steel mesh as a new type of durable reinforcement in structural members.